Transient velocity and steady state entropy generation in a microfluidic Couette flow containing charged nano particles - Gorla, Rama Subba Reddy; Gireesha, B. J. (Zielona Góra: Uniwersytet Zielonogórski)
An analysis has been provided to determine the transient velocity and steady state entropy generation in a microfluidic Couette flow influenced by electro-kinetic effect of charged nanoparticles. The equation for calculating the Couette flow velocity profile is derived for transient flow. The solutions for momentum and energy equations are used to get the exact solution for the dimensionless velocity ratio and dimensionless entropy generation number. The effects of the dimensionless entropy generation number, Bejan number, irreversibility ratio, entropy generation due to fluid friction and due to heat transfer on dimensionless time, relative channel height, Brinkman number, dimensionless temperature ratio, nanoparticle volume fraction are analyzed.
Keywords: transient velocity; steady state entropy generation; microfluidic Couette flow; charged nanoparticles; Bejan number and Brinkman number